2006
DOI: 10.1590/s0004-282x2006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and electric senoidal current stimulation

Abstract: -Objective: To analyze the relationship between perceptions and electrical senoidal curre n t stimulation (ESCS). Method: The study population comprise 100 healthy volunteers. ESCS of 5 Hz and 2 kHz were applied to the left index finger at one and 1.5 sensory threshold. Following each stimulus train a list of eight words (four related to thin fiber sensations and four related to thick fiber sensations) was p resented to the subjects who were asked to choose the three words closer to the experienced sensation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Results related to sensory perception (Table 3) are similar to those found in works of Tierra-Criollo et al (2006) and Pimentel et al (2006), which suggested that sinusoidal electrical currents at 5 and 2,000 Hz evoke different sensations. According to Félix et al (2009), stimuli at 2,000 Hz would activate Aβ-fibers while stimuli at 5 Hz would activate Aβ-, Aδ-, and C-fibers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results related to sensory perception (Table 3) are similar to those found in works of Tierra-Criollo et al (2006) and Pimentel et al (2006), which suggested that sinusoidal electrical currents at 5 and 2,000 Hz evoke different sensations. According to Félix et al (2009), stimuli at 2,000 Hz would activate Aβ-fibers while stimuli at 5 Hz would activate Aβ-, Aδ-, and C-fibers.…”
Section: Discussionsupporting
confidence: 89%
“…The classification errors led to a better class separation for Arrangement 2 (1, 250, and 3,000 Hz) than Arrangement 1 (5, 250, and 2,000 Hz), the latter widely used in literature for the evaluation of peripheral nervous fibers (Hedman andSullivan, 2011, Lowenstein et al, 2008;Matsutomo et al, 2005;Nishimura et al, 2004;Pimentel et al, 2006). Additionally, it was possible to verify that classification errors occur mainly at low and medium frequencies, for both arrangements, suggesting that such stimuli can activate similar fiber groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were allowed to a forced choice maximum of three words from the list. Similar methodology was employed in previous studies [16,24,25]. In addition, participants were asked to mark a line indicating stimulation subjective discomfort perceived in a continuous line, whose extremities ranged from "No discomfort at all" to "Extremely uncomfortable".…”
Section: Cognitive Evaluationmentioning
confidence: 99%